2018
DOI: 10.1017/gov.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Payoff Salience in Coalition Allocation: Ministers, Deputy Ministers and Committee Chairs

Abstract: Research during the past six decades has found that parties joining coalition governments receive payoffs, in the form of government posts, in proportion to their coalition share. These findings, however, do not indicate which coalition partners receive payoffs that will most enable them to influence their preferred policies. This article joins recent qualitative analyses of coalition allocation and examines payoffs in terms of the salience of positions relative to the policy goals of the parties receiving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Second, policy salience influences not only which departments parties pursue as coalition payoffs (Bäck et al 2011; Ecker et al 2015; Raabe and Linhart 2015) but also which committee chair positions they seek to obtain (Evans 2020). Previous research has also shown that there is a higher likelihood of shadowing by junior ministers when the department deals with a more salient policy area (Lipsmeyer and Pierce 2011).…”
Section: Committee Chair Shadowing: Previous Evidence and New Hypothesesmentioning
confidence: 99%
“…Second, policy salience influences not only which departments parties pursue as coalition payoffs (Bäck et al 2011; Ecker et al 2015; Raabe and Linhart 2015) but also which committee chair positions they seek to obtain (Evans 2020). Previous research has also shown that there is a higher likelihood of shadowing by junior ministers when the department deals with a more salient policy area (Lipsmeyer and Pierce 2011).…”
Section: Committee Chair Shadowing: Previous Evidence and New Hypothesesmentioning
confidence: 99%
“…Sieberer and Höhmann (2017) consequently present a comparative study of the formal powers of agenda setting of committee chairs but find that chairs in most countries have only few formal powers—yet, it is unclear how much actual power chairs can wield with only one or two formal prerogatives of setting the agenda. Previous studies suggest that chairs are in fact consequential by the way these positions are divvied up by coalition partners (Evans 2020), which strategically allocate chair positions among each other to ensure mutual checks and balances within the coalition (e.g., Carroll and Cox 2012; Kim and Loewenberg 2005). In particular, parties in coalition government make use of their committee chairs to amend unloved proposals by their government partners (Fortunato, Martin, and Vanberg 2019; Krauss, Praprotnik, and Thürk 2021) or to deter legislative initiatives of the coalition partner in that jurisdiction altogether (Fujimura, 2019).…”
mentioning
confidence: 99%